Effect of insecticides on pest incidence in summer greengram (Phaseolus radiatus) - Borah, R K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during summer season of 1993 and 1994 to find out the effect of synthetic pyrethroids, viz cypermethrin (0.01 and 0.015%) and deltamethrin (0.0028 and 0.0042%), along with dimethoate (0.03 and 0.045%) and malathion (0.05 and 0.075%) on pest incidence in green gram (Phaseolus radiaitus L,). The synthetic pyrethroids and dimethoate were found the most effective for controlling pest incidence in greengram. Malathion (0.05 and 0.075%) did not perform better than the control both for pest incidence as well as yield of green gram.